A Review on Tramiprosate (Homotaurine) in Alzheimer's Disease and Other Neurocognitive Disorders - Manzano, Sagrario; Agüera, Luis; Aguilar, Miquel; Olazarán, Javier (Frontiers in Neurology, 2020)
Alzheimer’s disease (AD) is the most prevalent neurodegenerative condition, especially among elderly people. The presence of cortical β-amyloid deposition, together with tau phosphorylation and intracellular accumulation of neurofibrillary tangles (NFT) is the main neuropathologic criteria for AD diagnosis. Additionally, a role of inflammatory, mitochondrial, and metabolic factors has been suggested. Tramiprosate binds to soluble amyloid, thus inhibiting its aggregation in the brain. It reduced oligomeric and fibrillar (plaque) amyloid, diminished hippocampal atrophy, improved cholinergic transmission, and stabilized cognition in preclinical and clinical studies. In this narrative review, current information on the efficacy and safety of tramiprosate, both in AD and in other neurocognitive disorders, is presented. Possible directions for future studies with tramiprosate are also discussed.